A Study On The Optimization And Adsorption Capacity Of Activated Carbon Produced From Polyvinyl Chloride (PVC) Wastes - Alabi-Babalola, O.D.; Aransiola, E.F.; Shittu, T.D. (Ife Journal of Technology, 2019)
Activated carbon (AC) was prepared by the pyrolysis of polyvinyl chloride (PVC) wastes. This was with a view to optimize and study its adsorption capacity through various activation processes. The optimization study was carried out using the central composite design of the response surface methodology (RSM). The effects of the reaction conditions: carbonization temperature (400 – 500 oC), concentration of chemical activating agents (0.50 – 2.00 M H2SO4 and KOH) and activation time (45 – 60 min) on the yield and other physicochemical properties were investigated. The study revealed that an optimum yield of 80 % was achieved at an average activation time of 48-50 min, and average temperature of 425-450 oC. Maximum adsorption capacity was obtained at optimized reaction conditions of 0.50 M, and 500 oC. However, the optimum time for both PVC-H2SO4 and PVC-KOH are 46.46 and 55.35 min respectively. Fourier transform infrared (FT-IR) analysis revealed the presence of oxygen-surface complexes such as the carbonyls and O-H groups on the surface of the AC which was due to chemical activation. Scanning electron microscope (SEM) analysis shows the presence of pores and cave-type openings on the carbon surface sites, thus, confirming the porosity in the carbons. The adsorption data was found to perfectly fit the Freundlich model at an adsorbent dosage of 0.75 g/100 mL of adsorbate. Equilibrium was reached between 60 and 75 min. The kinetic studies showed that the pseudo-second-order model provides the best correlation for the dynamic behaviour for the sorption of inorganic ions onto AC with a kinetic rate constant of 0.0178 min-1 and correlation coefficient of 0.9988.